2018
DOI: 10.1002/pssa.201700846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Versatile Immobilization Methods for Gram‐Positive Bacteria on a Silicon Cantilever

Abstract: Force spectroscopy and especially single cell force spectroscopy with bacterial probes provide a powerful tool for the investigation of bacterial adhesion to different surfaces. Thereby, a crucial step is the immobilization of the bacteria on the cantilever. Until today, there have been developed versatile methods to attach bacteria to a cantilever, but only few studies compare these methods in a quantitative way. In this work, different functionalizations of the cantilever as well as two picking-up parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…While focusing on the FluidFM, we implement measurement parameters for an SCFS measurement routine for Lactococcus lactis. A previous study showed that none of the typically used chemical immobilization methods leads to a reliable attachment of the cells without at the same time changing their surface properties [24]. Therefore, we used the FluidFM to physically immobilize the bacteria on the opening of a FluidFM cantilever and determined parameters for recording force-distance curves.…”
Section: Introductionmentioning
confidence: 99%
“…While focusing on the FluidFM, we implement measurement parameters for an SCFS measurement routine for Lactococcus lactis. A previous study showed that none of the typically used chemical immobilization methods leads to a reliable attachment of the cells without at the same time changing their surface properties [24]. Therefore, we used the FluidFM to physically immobilize the bacteria on the opening of a FluidFM cantilever and determined parameters for recording force-distance curves.…”
Section: Introductionmentioning
confidence: 99%
“…While focusing on the FluidFM, we implement measurement parameters for a SCFS measurement routine for Lactococcus lactis. A previous study showed that none of the typically used chemical immobilization methods leads to a reliable attachment of the cells without at the same time changing their surface properties [20]. Therefore, we used the FluidFM to physically immobilize the bacteria on the opening of a FluidFM cantilever and determined parameters for recording force-distance curves.…”
Section: Introductionmentioning
confidence: 99%